Fudge & jury - Alexander, Ellie (Alexander, Ellie. Bakeshop mystery., 2017)
"A world-renowned chocolatier has just turned up dead...right after sampling a slice of Jules' decadent four-layer chocolate cake. Now all eyes are on Jules as she tries to find the mysterious ingredient in her own recipe."--Provided by the publisher